Neuromonitoring, Cerebrospinal Fluid Drainage, and Selective Use of Iliofemoral Conduits to Minimize Risk of Spinal Cord Injury During Complex Endovascular Aortic Repair. (February 2016) - Banga, Peter V.; Oderich, Gustavo S.; Reis de Souza, Leonardo; Hofer, Jan; Cazares Gonzalez, Meaghan L.; Pulido, Juan N.; Cha, Stephen; Gloviczki, Peter
Purpose: To review outcomes of continuous motor/somatosensory-evoked potential (MEP/SSEP) monitoring, cerebrospinal fluid drainage, and selective use of iliofemoral conduits in patients undergoing endovascular repair of descending thoracic aneurysm (DTA) and thoracoabdominal aortic aneurysms (TAAAs).Methods: The clinical data of 49 patients (mean age 75±8 years; 38 men) who underwent endovascular repair of DTA and TAAAs (2011–2014) were reviewed. All patients had cerebrospinal fluid drainage, permissive hypertension (mean arterial pressure ≥80 mm Hg), and MEP/SSEP monitoring. There were 44 (90%) patients with TAAAs and 5 (10%) with DTA. Types I and II TAAAs were repaired in staged procedures. Iliofemoral conduits were used for small iliac arteries and to minimize time of lower extremity ischemia in patients with difficult anatomy. In patients with changes in MEP/SSEPs, a standardized protocol was employed to optimize spinal cord perfusion and restore lower extremity blood flow. Endpoints were mortality, spinal cord injury (SCI), and lower extremity ischemic complications.Results: Sixteen (33%) patients had staged TAAA repair. A total of 163 visceral arteries were targeted by fenestrations and branches (mean 3.7±1.0 vessels/patient). Temporary iliofemoral conduits were used in 16 limbs/14 patients. A stable MEP/SSEP was achieved in all patients. Thirty-one (63%) patients had a ≥75% decrease in MEP/SSEP amplitude in 50 limbs starting on average 75±28 minutes after obtaining vascular access. MEP/SSEP amplitude improved with maneuvers in 12 (39%) patients and returned to baseline with restoration of lower extremity flow in all except 1 patient who developed immediate SCI. Thirty-day mortality was 4%. Three (6%) patients had SCI, 2 permanent and 1 temporary at 14 days. There were no lower extremity ischemic complications.Conclusion: Neuromonitoring predicted immediate SCI and allowed use of a protocol to optimize spinal cord and lower extremity perfusion during complex endovascular aortic repair. Larger clinical experience is needed to evaluate the efficacy of neuromonitoring to prevent SCI.